Negotiations of the "New World" The Omnipresence of "Global" as a Political Phenomenon - Selchow, Sabine (Global Studies, 2016)
Global is everywhere - recent years have seen a significant proliferation of the adjective "global" across discourses. But what do social actors actually do when using this term? Written from within the political studies and International Relations disciplines, and with a particular interest in the US, this book demonstrates that the widespread use of "global" is more than a linguistic curiosity. It constitutes a distinct political phenomenon of major importance: the negotiation and reproduction of the "new world". As such, the analysis of the use of "global" provides fascinating insights into an influential and politically loaded aspect of contemporary imaginations of the world.